Forum shopping in times of crisis: a directors' duties perspective - Mevorach, Irit (De Gruyter, 2013)
Some systems have more efficient legal frameworks for insolvency than other regimes, thus directors of troubled companies may seek opportunities abroad. Yet, the legitimacy of forum shopping in close proximity to insolvency is debatable in the context of cross-border insolvency regimes. This paper examines the forum shopping phenomenon from a new perspective, that of directors’ duties in times of financial trouble, specifically in light of emerging international standards in this area. This method allows unearthing the degree to which forum shopping is legitimate. This paper also shows how the directors’ duties regime is better fit to deal with illegitimate forum shopping compared with cross-border insolvency frameworks.